A research review on healthy lifestyle of university students through statistical approach - Ong, Ai Lee; Sufahani, Suliadi (International Journal of Multidisciplinary Research and Development, 2018)
This paper shows different methods to analyse the survey questions that related to healthy lifestyle or the factors affect it. The factors included eating habits, health factors, exercise and entertainment. The steps normally start with survey method which there are many types of method to undergo data collection and then undergo the pilot study. In descriptive summary, it is needed to obtain the essential part of information in the whole study first before undergo analysis. Data analysis included some statistical tests are done to know the association within variables. There are also some methods that were used to measure the satisfaction level of the consumers in the organisations.